The landcape aspects of the historic city (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2024)
The increasing interest that in the last decades scholars have shown for the landscape, intended as a visual expression of the structure of a territorial area, has opened up promising perspectives for the cities’ studies, offering also new methodological keys for interpreting their building history.The landscape that unfolds in front of our eyes is the result of land transformations induced over time by human activities, except in rare areas that have remained intact in their state of nature. Towns – both large cities and smaller rural centers – are the manifestation of these transformations. As nodal components in functional terms and the organization of material structures, they have been decisive in the building processes of human habitats, according to their size, location, and vitality. They carried a significant weight about the network of material and immaterial relations that have innervated the territory, but also to its concrete image; so as to become more or less extensive characteristic elements of the landscape, places in which cultural values had been thickened up to becoming identity components of that places.